Assessment of Students Perception of the Ban Imposed by the Food and Drugs Authority on Celebrities from Advertising Alcoholic Beverages : A Case of the Ghana Institute Of Journalism - Korlekie, Korley Nissi (UniMAC-GIJ, 2020)
Celebrities are personalities that are well known in public either because of their credibility or attractiveness or because of both. To leverage this, alcoholic beverage companies use celebrities in their advertisement to increase the effectiveness and heighten the credibility of commercials. Research has proven that celebrity endorsement of alcohol does cast its impact, but other schools of thought attest the contrary. This study moves on the same line and affirms the impact of celebrity endorsement on customers buying intention. It will identify the factors that lead to celebrity’s influence audience and also examine the effect of celebrity endorsement in advertisement. The impact of banning celebrity advertisement of alcohol in Ghana and the general perception of the public on the ban is a main aim of the study. The study presents key findings on the issue to inform policymakers, companies, advertising firms, consumer groups and non-governmental organizations on the topic of restricting celebrities from advertising any alcoholic beverage.
Thesis